High-Throughput and Low-Cost Terahertz All-Dielectric Resonators Made of Polymer/Ceramic Composite Particles - Daquan Yang; Chao Zhang; Ke Bi; Chuwen Lan (IEEE Photonics Journal)
In this paper, we report a new and generic method for all-dielectric resonators operating at terahertz (THz) frequencies based on polymer/ceramic composite particles. In this method, the polymer solution is added into ceramic powders (strontium titanate) and prilling technology is employed to make them become polymer/ceramic composite micro particles. The prepared micro particles are then assembled as single-layer all-dielectric resonators. By using a THz time-domain spectrometer, we find that various Mie resonances can be induced in these all-dielectric resonators. It is also demonstrated that the permittivity of the composite particles can be improved by being sintered at proper temperatures, thereby provides a new way for ceramic all-dielectric resonators in THz range. This method, free from complex process, time-consuming, expensive equipment, and clean room, provides a generic method for high-throughput and low cost THz all-dielectric resonators, which is promising for developing potential applications in wide-bandwidth THz devices.